Abnormalities of T-cell subsets in patients with neutropenia and an excess of lymphocytes in the bone marrow. - Linch, D; Cawley, J; Worman, C; Galvin, M; Roberts, B; Callard, R; Beverley, P (1981)
Morphological, surface-marker and culture studies were performed in three patients who had in common neutropenia and an excess of lymphocytes in the bone marrow, but who differed from each other in certain regards such as age and peripheral lymphocyte numbers. All three patients had an increased proportion of E-rosetting cells bearing Fc receptors for IgG. These cells were shown to be T lymphocytes by staining with monoclonal anti-T-cell sera and their subset phenotype was established as OKT4- OKT8+; in addition, a variable proportion of the cells was Ia+. The functional significance of this expanded subpopulation of T cells was not clear, but it was shown that they did not inhibit colony formation in vitro.